The Efficiency Capture on Friendly Modification Boat Seine in Kendal District, Central Java - Fitri, Aristi Dian Purnama; Asriyanto, Asriyanto; Setiyanto, Indradi; Kurohman, Faik (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2011)
Boat seine is fishing gear in coastal areas consisting of wings and cod (bag). Target catch seine boat in the waters of Spring Sikucing-Weleri was rebon  (shrimp) and fish.  Boat seine problems that exist due to the  large hydrostatic  pressure,  the  number  of  crew (ABK)  and  size  of  a  lot of  fish  are  juvenile  (<10  cm  TL).  Aimed of modification  boat seine  at improving  the  technical efficiency of fishing that will affect the  increased  welfare of fishermen, as well as making environmentally-friendly fishing gear.Modification of the boat seine was located on the wing with nylon netting material change to 380 d / 9, and 7 mm mesh size. Number of crew (ABK) during hauling into 6-8 people, not the garbage that carried during the arrest operation, and the catch of fish is not juvenile (> 15 cm TL). Keywords: Boat seine modification, Effective, Efficiency and Selective